Development of facial, hand, and feet edema due to aripiprazole use with sertraline - Baykara, Sema; Korkmaz, Sevda; Korucu, Tuba (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2016)
Aripiprazole, a novel antipsychotic agent, is considered to be a dopamine-serotonin system stabilizer. It is from the dihydroquinolone group. It has been widely used in the treatment of schizophrenia, bipolar disorder, major depressive disorder, and anxiety disorders. Typical and atypical antipsychotics are known to cause cardiovascular side effects, but there is limited data on aripiprazole. During the treatment of an inpatient diagnosed with obsessive-compulsive disorder, edema occurred on the face, hands, and feet when the treatment was augmented with aripipirazole.
Keywords: aripiprazole; edema; obsessive-compulsive disorder